Synthesis of material interception networks with p-graph - Lim, C. H. (Animo Repository, 2017)
A P-graph model was recently developed for direct reuse/recycle scheme for both in-plant resource conservation networks (RCNs) and inter-plant RCNs (IPRCNs). The proposed P-graph model allows visualization which expedites the assessment of optimal and near-optimal solutions. In this paper, the P-graph model will be extended to material interception schemes, i.e., material regeneration and pre-treatment. Material regeneration involves the use of purification unit for quality improvement of the process sources before they are reused/recycled to the sinks. Pre-treatment processes, on the other hand, involve the purification of fresh resources for use in processes with stringent quality requirement. Two literature case studies are solved to demonstrate the newly extended model. © 2017, Springer Nature Singapore Pte Ltd.